The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24256/ideas.v8i2.1660
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Comic in Developing Student's English Competence

Abstract: This current study is aimed to know whether any improvement or not in using digital comics as the media on student’s English competence. The researchers used a quantitative approach with a pre-experimental design. This research was conducted at Universitas Muhammadiyah Lamongan and the sample was 42 pharmacist medical students. The instrument that was used to measure students’ English competence was the Test of English as a Foreign Language (TOEFL). The result of the test was analyzed by using statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The researcher concluded that authentic materials boost students' vocabulary based on the findings of the study and conversation. These findings are pertinent and support prior research by Ranker, 2007;Apriani et al, 2014;Rokhayani & Utari, 2014;Cimermanová, 2015;Issa, 2018;Nurkholida, 2018;Fatimah et al, 2019;Ahsanah & Utomo, 2020;Robbani & Khoirotunnisa, 2021. As a consequence, the findings of this study can be used as a resource for authentic information to help students enhance their vocabulary mastery.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…The researcher concluded that authentic materials boost students' vocabulary based on the findings of the study and conversation. These findings are pertinent and support prior research by Ranker, 2007;Apriani et al, 2014;Rokhayani & Utari, 2014;Cimermanová, 2015;Issa, 2018;Nurkholida, 2018;Fatimah et al, 2019;Ahsanah & Utomo, 2020;Robbani & Khoirotunnisa, 2021. As a consequence, the findings of this study can be used as a resource for authentic information to help students enhance their vocabulary mastery.…”
Section: Hypothesis Testingsupporting
confidence: 87%
“…According to a review of the literature researchers have reviewed, the steps teachers must take to teach creative thinking are similar to the way to think critically. Teachers should also have discussions in class to discuss the context previously given with digital comics (Ahsanah & Utomo, 2020;İlhan et al, 2021;Linardatos & Apostolou, 2023;Pratiwi & Palupi, 2022;Rutta et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini melihat penggunaan komik digital dalam pemahaman membaca siswa dan bagaimana komik digital mengembangkan kreativitas siswa dalam belajar. Penggunaan komik digital dalam pengajaran banyak Inggris membantu guru dan siswa untuk memahami bacaan (Ahsanah & Utomo, 2020;İlhan et al, 2021;Istiq'faroh et al, 2020;Khotimah et al, 2020) Kegiatan pengabdian ini menjadi berbeda dengan yang lain karena menggunakan dua hal yang berbeda dalam pengajaran bahasa Inggris yaitu strategi PQRST dan komik digital dalam pengembangkan kemampuan pemahaman membaca masyarakat pendidik di salah satu sekolah menengah di Barru.…”
Section: Pendahuluanunclassified